HIPOTEKA PRZYMUSOWA JAKO FORMA ZABEZPIECZENIA WYKONANIA ZOBOWIĄZAŃ PODATKOWYCH - Makowiec, Aneta (Zeszyty Prawnicze, 2016)
The Judicial Mortgage: A Form of Securing Tax Liability Summary This paper incorporates a characterisation and a thorough dogmatic analysis of the judicial mortgage as a form of securing the satisfaction of tax liabilities in Polish law. The significance of this issue warrants a discussion of the research both on its practical and theoretical aspects. In addition there has not been much interest in this subject in the Polish tax and legal literature. Undoubtedly, the amendments introduced during the last few years have prompted numerous questions and doubts with regard to these issues, which justifies the need for such research all the more. The fact that securing the satisfaction of tax liabilities is performed by employing methods well-known in civil law connected with liability involving rights in rem such as the mortgage, and the insufficient regulations regarding the judicial mortgage in tax law have made it necessary to analyse the legislation on private law as well as the doctrines and case-law connected with it.